Prenatal passive smoking at home: The experiences of women in Thailand - Idchayar Mornsaeng; Kasara Sripichyakan; Nantaporn Sansiriphun; Nonglak Chaloumsuk (Belitung Raya Foundation, Indonesia, 2024)
Background: Passive smoking poses a threat to the well-being of an unborn baby; however, women’s understanding and practice in this regard remain unclear. Objective: This study aimed to describe prenatal passive smoking at home based on the experiences of women in Thailand. Methods: A qualitative descriptive approach was employed. Data were collected between September 2020 and April 2022 through semi-structuredin-depth interviews with 16 postpartum women purposively selected from five hospitals. Thematic analysis was used for data analysis. Results: Three themes emerged. The first theme, ‘safeguard for an unborn baby,’ was performed through smoking reduction, far distance, abstinence from smoke/odor inhalation, and residual elimination since harm was highly aware. However, justifying safety from the absence of smoke and foul odor was misperceived. The second theme, ‘intervention for smoking cessation,’ was attempted through various methods, including acquired empathy, persuasion, compromise, and supportiveness. They also needed family/friend assistance in warning and professional care in terms of advice, health education, learning materials, cessation therapy, care continuation, and dealing with complex situations. The last theme, ‘maternal perseverance,’ was acquired by the motives of safety goals, rights/responsibilities, changeable norms, and a golden period. Conclusion: Pregnant women persistently aimed to prevent their husbands from smoking and safeguard their unborn babies from passive smoking. However, misunderstandings and improper practices were observed. Healthcare and nursing services need comprehensive approaches to enhance understanding, perseverance, and tailored practices catering to women’s needs.